2017
DOI: 10.1002/rob.21705
|View full text |Cite
|
Sign up to set email alerts
|

Rice Autonomous Harvesting: Operation Framework

Abstract: This paper reports on an operation framework for autonomous rice harvesting. We developed an integrated algorithm for robotic operation and cooperation with farmworkers to automate each subsection of the harvesting and unloading process and of the processes that bridge them (homing and restarting). The algorithm was installed into a head‐feeding combine robot. The robot followed a target path based on its absolute position and orientation, planning a counterclockwise spiral path in a rectangular paddy field, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Since the distance between rows of rice is 30 cm, even if an error of about 5 cm occurs during driving, it is judged that it is within the allowable error because there is no non-working area. The results tested in the previous study showed that the average working path error was 0.03–0.04 m at a maximum speed of 3.6 km/h [ 17 ] and 0.07 m at a maximum speed of 2.3 km/h [ 19 ]. In this paper, the average work path error was 0.04 m, so there was no significant difference, but the work travel speed was 6 km/h and had a stable performance at a higher speed.…”
Section: Discussionmentioning
confidence: 99%
“…Since the distance between rows of rice is 30 cm, even if an error of about 5 cm occurs during driving, it is judged that it is within the allowable error because there is no non-working area. The results tested in the previous study showed that the average working path error was 0.03–0.04 m at a maximum speed of 3.6 km/h [ 17 ] and 0.07 m at a maximum speed of 2.3 km/h [ 19 ]. In this paper, the average work path error was 0.04 m, so there was no significant difference, but the work travel speed was 6 km/h and had a stable performance at a higher speed.…”
Section: Discussionmentioning
confidence: 99%
“…The sugarcane harvester machine combined with machine vision algorithm detects the damaged billets, consequently increasing the quality of the production [48]. The autonomous rice harvester with a combined robot performed harvesting, unloading and restarting with adequate accuracy [49]. The autonomous harvesting grippers with machine vision locate target like peduncles for various crops and remove the leaves and stems as obstacles to improve the harvesting system [50].…”
Section: Unmanned Ground Vehicles (Ugvs)mentioning
confidence: 99%
“…Many research projects have been performed, but little has filtered through into the commercial world. The more successful projects include a harvester for apples (Silwal et al, ) using a suction method, rice harvesting using custom harvesting systems (Kurita, Iida, Cho, & Suguri, ), and a sweet pepper harvesting system (Bac et al, ). There has also been significant work in the development of autonomous weeding or grading systems including a sugar beet classifying system (Lottes, Hörferlin, Sander, & Stachniss, ) and a grape pruning system (Botterill et al, ).…”
Section: State Of the Artmentioning
confidence: 99%